2012
DOI: 10.1016/j.jweia.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of cross-ventilation flow for different isolated building configurations: Validation with wind tunnel measurements and analysis of physical and numerical diffusion effects

Abstract: a b s t r a c tComputational Fluid Dynamics (CFD) has become one of the most important tools for the assessment of natural cross-ventilation of buildings. To ensure the accuracy and reliability of CFD simulations, solution verification and validation studies are needed, as well as detailed sensitivity studies to analyse the impact of computational parameters on the results. In a previous study by the present authors, the impact of a wide range of computational parameters on the cross-ventilation flow in a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 44 publications
3
79
0
2
Order By: Relevance
“…Skovgaard and Nielsen 1990;Jones and Whittle 1992;Ramponi and Blocken 2012a). In 1992, Jones and Whittle (1992) stated in their overview paper that sufficient grid resolution should be applied in jet regions, boundary layers and in thermal plumes, and that: "A failure to provide enough mesh in these areas will result in the supply jet or the boundary layer flow being insufficiently resolved (where the momentum is rapidly and artificially diffused) resulting in an unrealistic local (and possibly global) solution.".…”
Section: Grid Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skovgaard and Nielsen 1990;Jones and Whittle 1992;Ramponi and Blocken 2012a). In 1992, Jones and Whittle (1992) stated in their overview paper that sufficient grid resolution should be applied in jet regions, boundary layers and in thermal plumes, and that: "A failure to provide enough mesh in these areas will result in the supply jet or the boundary layer flow being insufficiently resolved (where the momentum is rapidly and artificially diffused) resulting in an unrealistic local (and possibly global) solution.".…”
Section: Grid Resolutionmentioning
confidence: 99%
“…Sørensen and Nielsen 2003;Ramponi and Blocken 2012a) reported that the effect of numerical (artificial) diffusion can be compared to the physical diffusion caused by the turbulence in CFD simulations. Both physical and numerical diffusion smear out the results and a high level of numerical diffusion will negatively impact the numerical accuracy.…”
Section: Physical Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second-order discretization scheme is used to interpolate pressure from values at cell centers. The convergence criteria, based on the scaled residuals, are set to 4 1 0 − for all variables. Before simulations were terminated, the predicted values of the variables of interest were constant.…”
Section: 3) Wind Predictions At Unmeasured Locationsmentioning
confidence: 99%
“…Wind can also be harnessed for natural ventilation of buildings [2]. Computational Fluid Dynamics (CFD) simulations have been widely used to simulate wind around and through buildings [3,4]. Although guidelines have been established to improve simulation predictions [5], large discrepancies remain when simulation predictions are compared to field measurements.…”
Section: ) Introductionmentioning
confidence: 99%